Dynamic analysis of the tower crane / Hamid Nalbandian Abhar - Hamid , Nalbandian Abhar (2013)
Tower cranes are amongst the most important machines used in industrial activities; therefore, understanding the natural frequency of these structures for optimal performance remains an essential field of study. Vibration, from an origin such as ‘Swing of the payload’, creates a dynamic load on the tower crane structure which may result in fatigue, weakness and ultimately collapse of the crane. The purpose of this thesis is to identify the dynamic behavior of planar model tower cranes under the pendulum motions of the payload. By doing this, hypotheses will be generated that may aid in improving the performance and safety of the crane. In this thesis, Pendulation motion equations, after adjusting for cable stiffness along the crane’s jib, will be defined based on the Lagrange Equations and solved using the numerical method based on the Runge-Kutta fifth order. The crane will be modeled and analysed using finite element software (FEM), and the first few natural frequencies of the complex planar model will be compared by analytical methods in order to verify the data. Continued load effects will be determined by the numerical solution of differential equations, and these will be entered into the finite element software for the purpose of analysis. Research results will present any changes in the effect of vibration, such as stress and deformation, when the payload is placed at different positions along the crane’s jib and body